Os personagens negros na literatura brasileira oitocentista: representação do negro nas obras abolicionistas Úrsula, de Maria Firmina dos Reis e as vítimas-algozes, de Joaquim Manuel de Macedo - SILVA, Tatiane Da Conceição Marques (2023)
The object of study and general argument of this investigation was the study of the representation of the Black in two nineteenth-century works: Úrsula, by Maria Firmina dos Reis, and The Executioner-Victims, by Joaquim Manuel de Macedo. Both of the researched authors are considered as abolitionists, however, each one of them has a different point of view as to the Black and these distinct conceptions are reflected in their writing by means of the making of the black characters in many ways. As a means to carry out this research, its general aim was to analyze the representation of the Black in the works Ursula and The Executioner-Victims, verifying if the authors depict the Black as an object or as a subject. In order to maintain this inquiry, comparativism was utilized as a method, whereas bibliographic and documental research was its methodological procedure, supported by the critical fortune of David Brookshaw (1983), Domício Proença Filho (2004), Evaristo de Morais (2019), Kabengele Munanga (2019), Marcos Francisco Alves (2012), José Antônio Dias de Abreu (2004), Laurentino Gomes (2019, 2021, 2022), among others, so as to answer to the problem questions and to base the matter addressed, verticalizing the analysis. In addition, as obtained results, it was noticed that the novel Ursula points out the abolition of slavery from the speech of the enslaved mentioning the voice, the history, the feelings, the emotions of the Black as a protagonist, this way, the Firminian text deconstructs stereotyped images of the enslaved black, detaching it from the idea of a mere object. Nevertheless, while Maria Firmina dos Reis writes with commitment and fights for the end of slavery in Brazil for humanitarian reasons, the abolitionism in the work The Executioner-Victims occurs in an inverted manner, Macedo ends up imprinting into slavery, for political and economic reasons, elements that make the slaveowners become the victims of the captive black. By means of the three stories in the book, the author constructs the image of the black as something demoniac, prevailing only negative stereotypes as to the Black, which permeated the nineteenth-century mentality. What can be observed, throughout the narrative, is the devaluation of the enslaved as a historical subject.